INTEGRATION OF TRADITIONAL AND MODERN WEB TECHNOLOGIES IN THE TRAINING OF JUNIOR SPECIALISTS IN THE FIELD OF FRONT-END DEVELOPMENT - LAVRIK, VOLODYMYR; NIKONOV, OLEG; NOVAK, DMYTRO (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article explores the integration of traditional and modern approaches in the training of Junior specialists in the field of front-end development. Emphasis is placed on the significance of HTML and CSS as foundational technologies that serve as the basis for acquiring core competencies in web development. The traditional methodology, which relies on a consistent, step-by-step mastery of syntax, manual code writing, and basic layout exercises, is analyzed as an effective model for building essential skills at the initial stages of professional training. However, given the accelerated pace of technological progress and the rising complexity of web applications, the article highlights the growing necessity of incorporating modern front-end tools and frameworks such as React, Vue.js, and Tailwind CSS. These technologies provide enhanced opportunities for building dynamic, scalable, and maintainable web interfaces and are increasingly demanded by employers. A comparative analysis of these frameworks is presented, covering their architecture, design philosophy, syntax, and suitability for learners at the beginner level. The study supports a blended instructional approach that begins with traditional technologies and progressively integrates contemporary tools. This educational trajectory promotes a deeper understanding of the principles underlying front-end development, while simultaneously equipping learners with the practical skills needed in real-world environments. The article concludes by outlining prospects for further research, emphasizing the need to design adaptive, modular, and scalable educational models that align with evolving industry standards and technological innovations. These findings will be especially relevant to educators, curriculum designers, and institutions aiming to modernize training programs and improve the employability of graduates in the competitive IT labor market.